213k views
4 votes
What does the equation y = x2 - 6x + 5 become after completing the square?

What does the equation y = x2 - 6x + 5 become after completing the square?-example-1
User Kmanzana
by
4.5k points

2 Answers

5 votes

Answer: Option B

Explanation:

Given the quadratic equation
y=x^2-6x+5
:

You know that:


((b)/(2))^2=((6)/(2))^2=3^2

Group the variable "x" inside a parentheses:


y=(x^2-6x)+

Then, now you need to add 3² inside the parentheses and subtract 3² outside of the parentheses. Thenrefore, rewriting, you get:


y=(x^2-6x+3^2)+(5-3^2)\\y=(x-3)^2-4

This matches with the option B.

User Vinibrsl
by
5.3k points
6 votes

Hello!

The answer is:

The answer is: C.


y=(x-3)^(2)-4

Why?

To answer this question, we need to remember the completing square process.

We can complete the square in the following way:

- Make the function equal to 0.

- Isolate the constant number (c).

- Find the number that completes the square using the following formula:


((b)/(2))^(2)

- Add the number that completes the square to both sides of the equation.

- Factorize the trinomial on one of the sides of the equation, and simplify the other side.

So, We are given the equation:


y=x^(2) -6x+5

- Making it equal to 0, we have:


0=x^(2) -6x+5

- Isolating the constant, we have:


x^(2) -6x=-5

- Finding the number that completes the square:


((b)/(2))^(2)=((-6)/(2))^(2)=(-3)^(2)=9

- Adding it to both sides of the equation:


x^(2) -6x+9=-5+9

- Factoring and simplifying, we have:


x^(2) -6x+9=-5+9

We need to find two numbers which product gives as result "9" and its algebraic sum gives as result "-6", this numbers is "-3", then, factoring, we have:


(x-3)^(2)=4


(x-3)^(2)-4=0

Then, the equation after completing the square will be:


y=(x-3)^(2)-4

Hence, the answer is:

C.
y=(x-3)^(2)-4

Have a nice day!

User Brian Cragun
by
5.7k points